Prostaglandin Gel: An Alternative to Caesarean Section in the Management of Post-dated Pregnancies with Unfavorable Cervices. - Chaudhury, Shipra; Khanam, Merina (TAJ: Journal of Teachers Association, 2009)
Fifty cases of post-maturity with unfavorable cervices were chosen to deliver the fetuses by the application of intracervical prostaglandin (PG) gel as an alternative to Caesarean section. The study was carried out in the Department of Obstetrics and Gynaecology, Rajshahi Medical College and Hospital. Rajshahi during the period from January 2001 to November 2002. Patients with [representations, premature rupture of membrane and history of previous two uterine Caesarean sections were excluded from this study. Gel was inserted above the cervical canal and re-administered every 6-8 hours interval for a period of 24 hours where necessary. Successful vaginal delivery was achieved in 98% of cases with adequate cervical ripening. Reinsertion of the gel was needed in only 8 cases. Oxytocin was used along with PG gel for initiation and augmentation of labour pain. Caesarean section was needed only in 1 patient and remaining all patients delivered within 24 hours of the onset of induction of this procedure. doi: 10.3329/taj.v15i2.3906 TAJ December 2002; Vol.15(2): 53-55